From franchisee to startup: The birth of LiHO bubble tea - RAMASWAMI, Seshan (Institutional Knowledge at Singapore Management University, 2020)
The case begins in 2009, when the Gong Cha franchise was launched in Singapore by entrepreneur Rodney Tang with a sole outlet in a mall. Within two years, the franchise expanded to 20 outlets, and another five years later, there were 80 outlets in the city-state, and Gong Cha had a well-established and loyal patronage. In 2016, when financial restructuring of the parent company led to some important changes in the operating clauses of the franchise agreement, Tang had to decide whether to extend the contract or to set up his own new chain. Taking away a brand, valued by so many loyal consumers (and one which might yet re-enter the Singapore market with a different operator), while introducing a new brand, located at the same outlets as the Gong Cha ones clearly presented some major challenges. Competitors like Koi, Sweet Talk and Each-a-Cup would also be looking to attract the loyal Gong Cha patrons. Establishing a new brand would have its own set of challenges. How could Tang differentiate from Gong Cha while not alienating the Gong Cha loyal consumer, especially when the original brand will likely return to the Singapore market? This case describes and highlights how a business owner had to switch out the popular Taiwanese Bubble Tea franchise Gong Cha for a new Singaporean brand LiHO within a very short period of just a week. Through this case study, students will learn about the key decisions made on branding, menu design, and innovation in the process of creating a new Singaporean brand with global ambitions.